Micro- and macro-borderless surgery using a newly developed high-resolution (4K) three-dimensional video system - Yagi, Shintaro; Ito, Takashi; Shirai, Hisaya; Yao, Siyuan; Masano, Yuki; Ogawa, Eri; Gabata, Ryosuke; Uemoto, Shinji; Kobayashi, Eiji (PloS one, 2021)
Microsurgery using conventional optical microscopes or surgical loupes features a limited field of view and imposes a serious strain on surgeons especially during long surgeries. Here we advocate the micro- and macro-borderless surgery (MMBS) using a novel high-resolution (4K) three-dimensional (3D) video system. This study aimed to confirm the applicability of this concept in several surgical procedures. We evaluated the possible use and efficacy of MMBS in the following experiments in porcine subjects. Experiment 1 (non-inferiority test) consisted of dissection and anastomosis of carotid artery, portal vein, proper hepatic artery, and pancreatoduodenectomy with surgical loupe versus MMBS. Experiment 2 (feasibility test) consisted of intra-abdominal and intra-thoracic smaller arteries anastomosed by MMBS as a pre-clinical setting. Experiment 3 (challenge on new surgery) consisted of orthotopic liver transplantation of the graft from a donor after circulatory death maintained by machine perfusion. Circulation of the cardiac sheet with a vascular bed in experiment 2 and liver graft during preservation in experiment 3 was evaluated with indocyanine green fluorescence imaging equipped with this system. Every procedure was completed by MMBS. The operator and assistants could share the same field of view in heads-up status. The focal depth was deep enough not to be disturbed by pulsing blood vessels or respiratory movement. The tissue circulation could be evaluated using fluorescence imaging of this system. MMBS using the novel system is applicable to various surgeries and valuable for both fine surgical procedures and high-level surgical education.